PEMBATALAN PENDAFTARAN MEREK KARENA ADANYA PERSAMAAN PADA POKOKNYA DENGAN MEREK TERKENAL YANG TIDAK TERDAFTAR - Oktavianus Sulis, Thio Aswin (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract : The main aim of this scientific journal is as a partial fulfillment of the requirement for the Bachelor of Law degree at the Faculty of Law of the University of Surabaya. The practical objective of this journal is to be used as references on behalf of the Intellectual Property rights, especially in trademark law. The conclusions are drawn as followed:marks must be registered first to obtain legal protection although it is a well-known marks in accordance witharticle3 of Law No.20of 2016,registerd mark will get certification which means it is legally valid and does not violate the provisions of article 20 jo. Article 21 of Law No.20 of 2016, and well-known mark cannot undo registered mark in good faith and already got certified for more than 5 (five) years in accordance with article 77 of Law No.20 of 2016. Keywords : marks, registered mark, well-known mark, Law No. 17 of 2016 on trademark and geographical indication.